PENGEMBANGAN APLIKASI E-COMMERCE DENGAN KONSEP BERORIENTASI OBJEK PADA PT SHARP CABANG SEMARANG - Arifian Rahman; Suhartono Suhartono; Nurdin Bahtiar (Jurusan Ilmu Komputer / Informatika, FMIPA UNDIP, Semarang, 2012)
PT Sharp Semarang branch is engage in the marketing of electronic items like air conditioners, refrigerators, televisions, and others. Business competition is increasingly fierce, especially in the electronics field requires the selection of advertising media that can market their goods quickly and easily. E-commerce as a new method that uses the Internet media is the right solution to market their goods easily and quickly. Application E-commerce Sharp Semarang developed using method of object-oriented software engineering (OOSE / Object Oriented Software Engineering). By using the method of object-oriented software engineering Application E-commerce Sharp Semarang is expected to has more quality in terms of functionality and the stage of develope